2016
DOI: 10.1177/1049732316672639
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and Constructions of Menarche and Menstruation Among Migrant and Refugee Women

Abstract: Experiences and constructions of menarche and menstruation are shaped by the sociocultural environment in which women are embedded. We explored experiences and constructions of menarche and menstruation among migrant and refugee women resettled in Sydney, Australia, and Vancouver, Canada. Seventy-eight semistructured individual interviews and 15 focus groups comprised of 82 participants were undertaken with women from Afghanistan, Iraq, Somalia, South Sudan, Sudan, Sri Lanka, and varying South American countri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 76 publications
1
44
1
1
Order By: Relevance
“…This qualitative study revealed the value which participants place on access to menstrual materials as well as the importance of sanitation infrastructure design and menstrual hygiene education, and is consistent with literature outlining the required components of an adequate MHM intervention. 4 , 16 Also, consistent with the literature were themes of secrecy and shame 17 , 18 and that the existence of cultural and religious beliefs was not expressively shared by all, regardless of similarities in country of origin and religious or cultural identity. 7 Practices were, however, homogenous in that external absorbent products were preferred.…”
Section: Discussionsupporting
confidence: 54%
“…This qualitative study revealed the value which participants place on access to menstrual materials as well as the importance of sanitation infrastructure design and menstrual hygiene education, and is consistent with literature outlining the required components of an adequate MHM intervention. 4 , 16 Also, consistent with the literature were themes of secrecy and shame 17 , 18 and that the existence of cultural and religious beliefs was not expressively shared by all, regardless of similarities in country of origin and religious or cultural identity. 7 Practices were, however, homogenous in that external absorbent products were preferred.…”
Section: Discussionsupporting
confidence: 54%
“…Discussion on social impacts of menstruation exists, though there remains a lack of research to quantify outcomes. 40 Two separate analysis 23 , 41 of one qualitative study exploring experiences of sexual embodiment and menstruation in migrants and refugees found recurring themes of shame, secrecy, and dirtiness among the multicultural participants. Additionally, themes of anxiety, fear, and distraction were found to be associated with menstruation.…”
Section: Resultsmentioning
confidence: 99%
“…The low usage of the oral contraceptive pill in the included studies is surprising, given that population surveys have shown an inverse relationship between contraceptive usage and self-reported period pain[5557] and the combined oral contraceptive (COC) is commonly recommended as a second line of treatment for primary dysmenorrhea if NSAIDs have been unsuccessful [5, 58]. The reasons for the lower usage in LMIC may be influenced by cultural or religious factors, especially in young or unmarried women due to concerns that the COC promotes sexual promiscuity [12, 59]. Usage of COC in HIC was significantly higher, but still considerably lower than using analgesics, even though many women reported lack of effective pain relief with analgesics.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some countries such as Sri Lanka, Nigeria and India, have traditionally held strong taboos related to menstruation [911]. This in turn may impact how women manage their menstrual pain due to their beliefs and attitudes and/or a lack of accurate information[12].…”
Section: Introductionmentioning
confidence: 99%